Mutans streptococci estimation in saliva before and after consumption of probiotic curd among school children - Bhalla, Manish (J Int Soc Prev Community Dent, 2015)
BACKGROUND: According to the World Health Organization, probiotics are live microorganisms which when administered in adequate amounts and confer a health benefit to the host. Use of probiotics in children to improve oral health may lead to non-pathogenic bacteria replacing cariogenic bacteria. Dairy foods like cheese, curd, and milk are considered useful vehicles for probiotic bacteria. AIM: To compare the levels of salivary mutans streptococci before and after consumption of probiotic curd. MATERIALS AND METHODS: Thirty school children of Mathura city who were caries free, in the age group of 12–14 years, were selected and divided equally into group I and II which were given 200 ml probiotic curd and normal curd for 7 days, respectively. Assessment of saliva samples was done at baseline, 1 h after consumption, and on the 7(th) day. Mitis Salivarius Bacitracin Agar was used for analysis. The number of colonies was counted and subjected to statistical analysis using unpaired Student's t-test. RESULTS: The study showed mark reduction in salivary mutans streptococci counts in saliva after 1 h and on the 7(th) day in the probiotic group. Results were found to be statistically significant (P ≤ 0.05) when the differences in the reduction of mutans streptococci counts with probiotic curd and normal curd at 1 h and on the 7(th) day were compared. CONCLUSION: Pathogenic microorganisms could be displaced by probiotic bacteria. Thus, use of probiotic products could be exploited for the prevention of enamel demineralization.